SISTEM INFORMASI MONITORING PENGANGGARAN DAN PENATAUSAHAAN - Asraf Humonggio; Sitti Suhada; Tajuddin Abdillah (Gorontalo State University, 2021)
Along with the rapid development of the times the need for data as well as accurate, fast, and informative information is very much needed, Gorontalo District Finance Agency was not spared from similar data requests. Presenting data in the old-fashioned way often degrades the quality of financial statements in accordance with Government Accounting Standards (GAS). This requires the agency that manages, monitors the budget and also the entrepreneurs of Gorontalo Regency to present data that is in line with current needs while maintaining existing standards. The purpose of this study is to apply the prototype method to collect the needs of the presentation of financial statements which are then made in a rapid design and implementation of the system, to submit it to the Financial Board in order to get feedback as testing material in order to produce a good system and in accordance with needs. The results of this study are the Budgeting and Monitoring Monitoring Information System using the prototype method, which is applied to the PHP programming language and MySQL storage, this application is expected to facilitate the Financial Agency in presenting financial reports that are not only accurate and fast but also more informative so that easy to understand.Keywords: Information Systems, Finance, Prototype, PHP, MySQL